Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Section 12.8 - Exponential and Logarithmic Equations and Problem Solving - Exercise Set: 51

Answer

$-\dfrac{5}{3}$

Work Step by Step

Given $\dfrac{x^2-y+2z}{3x} , $ if $x=-2 \ , \ y = 0$ and $z = 3$ $\dfrac{(-2)^2-0+2\times 3}{3\times (-2)} = \dfrac{4+6}{-6} = -\dfrac{10}{6} = -\dfrac{5}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.